Mechanical behavior comparison of spider and silkworm silks using molecular dynamics at atomic scale. Issue 6 (25th January 2016) - Lee, Myeongsang; Kwon, Junpyo; Na, Sungsoo
Abstract : Mechanical characteristics between spider and silkworm silks fibroins at nano scale are different owing to end serine residue in silkworm. Abstract : Spider and silkworm silk proteins have received much attention owing to their inherent structural stability, biodegradability, and biocompatibility. These silk protein materials have various mechanical characteristics such as elastic modulus, ultimate strength and fracture toughness. While the considerable mechanical characteristics of the core crystalline regions of spider silk proteins at the atomistic scale have been investigated through several experimental techniques and computational studies, there is a lack of comparison between spider and silkworm fibroins in the atomistic scale. In this study, we investigated the differences between the mechanical characteristics of spider and silkworm fibroin structures by applying molecular dynamics and steered molecular dynamics. We found that serine amino acids in silkworm fibroins not only increased the number of hydrogen bonds, but also altered their structural characteristics and mechanical properties.